2017
DOI: 10.3389/fimmu.2017.00706
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Homeostatic Impact of Age-Related Changes in Lymph Node Stroma

Abstract: Adults over 65 years of age are more vulnerable to infectious disease and show poor responses to vaccination relative to those under 50. A complex set of age-related changes in the immune system is believed to be largely responsible for these defects. These changes, collectively termed immune senescence, encompass alterations in both the innate and adaptive immune systems, in the microenvironments where immune cells develop or reside, and in soluble factors that guide immune homeostasis and function. While age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 70 publications
(157 reference statements)
2
50
0
1
Order By: Relevance
“…We observed significant differences of GC activity between young and old NHP LNs. The dark and the light zone were largely indistinguishable in many of the old follicles, in line with studies showing that the microenvironment of the LN is disrupted with age due to disruption of the FDCs, FRCs, and other stromal cells (Thompson et al, ). This altered GC organization was associated with significantly lower normalized numbers of Tfh and CD20 hi Ki67 hi GC B cells, suggesting disrupted mutual regulation between Tfh and GC B cells (Baumjohann et al, ) that could result in impaired steady‐state GC reactivity in old NHP LNs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed significant differences of GC activity between young and old NHP LNs. The dark and the light zone were largely indistinguishable in many of the old follicles, in line with studies showing that the microenvironment of the LN is disrupted with age due to disruption of the FDCs, FRCs, and other stromal cells (Thompson et al, ). This altered GC organization was associated with significantly lower normalized numbers of Tfh and CD20 hi Ki67 hi GC B cells, suggesting disrupted mutual regulation between Tfh and GC B cells (Baumjohann et al, ) that could result in impaired steady‐state GC reactivity in old NHP LNs.…”
Section: Discussionsupporting
confidence: 81%
“…Interrupting the cross‐talk between Tfh and B cells results in impaired GC formation and pathogen‐specific B‐cell responses in aged mice (Sage et al, ). Furthermore, mouse models have shown that aging impacts many of these populations including fibroblastic reticular cells (FRCs), a cellular network crucial for the survival of naïve T cells and trafficking of T cells within the extra follicular areas (Thompson, Smithey, Surh, & Nikolich‐Zugich, ), FDCs, vital for GC organization and antigen presentation to B cells (Aydar, Balogh, Tew, & Szakal, ), tissue macrophages, and Tfh and B cells (Eaton, Burns, Kusser, Randall, & Haynes, ; Turner & Mabbott, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, lymph nodes are in charge of both maintenance and coordination of new immune responses necessary to control viruses such as SARS-2. Lymph nodes undergo dramatic age-related changes in the final third of life, becoming less able to maintain naïve T cells (Thompson et al 2017) and to coordinate new immune responses to emerging infections Moreover, the T cells that do remain do not move quickly enough to meet innate immune cells when the infection strikes , which could be a consequence of dysregulation in chemokines that guide T cell migration. Innate immune cells themselves do not get activated by infection as efficiently in mice ) and humans .…”
Section: Immune Response To Coronaviruses and Sars-cov-2mentioning
confidence: 99%
“…The dependence of immunity on the immune microenvironment that is constructed by the supporting cellular players is apparent. Furthermore, there are reports on the negative effects of pathological perturbation of LN stroma on immune function . An appropriate and optimum amount of collagen and thickness of the collagen bundles of the reticulum network is important for lymphoid architecture and function.…”
Section: Deconstructing the Immune Microenvironment Of Lymphoid Tissuesmentioning
confidence: 99%